A sufficient condition for strong almost-periodicity of scalarly almost periodic representations of the group of real numbers - Kadets, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We prove the following theorem: If every separable subspace Y of a Banach space X has a separable weak sequential closure in Y **, then every scalarly almost periodic group acting in X is strongly almost periodic.